THE INFLUENCE OF PROFESSIONAL EDUCATION EXPERIENCE ON INNOVATIVE WORK BEHAVIOR OF TEACHER PROFESSIONAL EDUCATION ALUMNI - Ningrum, Fadhilah Atika; Suparno; Pratama, Aditya (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
This study aims to examine the effect of professional education experience on the innovative work behavior of teachers who are alumni of the Teacher Professional Education (PPG) program at Universitas Negeri Jakarta (UNJ). This study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to in-service PPG alumni at UNJ who had completed the program. The data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The results of the study indicate that professional education experience has influence on teachers' innovative work behavior. The greater the professional education experience gained during the PPG program, the higher the tendency for teachers to demonstrate innovative work behavior in their workplaces. These findings imply that the implementation of the PPG program can enhance teachers’ abilities to address learning challenges through the application of new ideas that are relevant to students' needs.